Breastfeeding Wages According to Al Quran and Al Sunnah - Daud, Normadiah (International Journal of Psychosocial Rehabilitation, 2020)
Payments for women who breastfeed a child has been widely discussed in the literature. Questions whether they should be paid with some amount of money arises in the community for such women who are in marital relationship or have been divorced. Nevertheless, wages for a woman who breastfeed a non-biological child and the consequence of such practice has also been inquired.. Hence this review aims to explore the jurists’ and the Islamic scholars’ debate on wages to a woman who breastfeed their biological as well as non-biological child. Qualitative methods were used in this review. Data from books of Islamic jurisprudence (Fiqh), and interpretation of had ith were analyzed. This review provides explanation of the criteria of breastfeeding women who deserve to receive wages, rate of the wages, timing of payment and the effect of such practice through Islamic lenses.